Synthesis and Characterization of 1,2-Benzenedimethyloxy Substituted Novel Ball-Type and Mononuclear Metallo Phthalocyanines - Yazici, Aysegul; Dalbul, Nida; Salih, Bekir (Chem Soc Pakistan, 2014)
The phthalodinitrile derivative 1 was synthesized by the reaction of 1,2-benzenedimethanol and 4-nitrophthalonitrile in dry DMF in the presence of K2CO3 by the common method of nucleophilic substitution of an activated nitro group in an aromatic ring. The template reaction of 1 with the corresponding metal salts gave the novel mono-nuclear ZnPc 2 and ball-type metallophthalocyanine LuPc2 3. In this study, we have used the heating of the solid phase'' method for the synthesis of novel ball-type LuPc2 3 phthalocyanines. Mono-nuclear ZnPc 2 phthalocyanine was prepared by reflax in solvent. Mono and ball-type phthalocyanines were characterized by elemental analyses, FT-IR, H-1-NMR, C-13-NMR, UV-vis and MALDI-TOF MS spectral data.
Keywords: Ball-type phthalocyanine; Zinc; Lutetium